2018
DOI: 10.1096/fj.201801799r
|View full text |Cite
|
Sign up to set email alerts
|

Secretome analysis of nerve repair mediating Schwann cells reveals Smad‐dependent trophism

Abstract: Schwann cells promote nerve regeneration by adaptation of a regenerative phenotype referred to as repair mediating Schwann cell. Down‐regulation of myelin proteins, myelin clearance, formation of Bungner's bands, and secretion of trophic factors characterize this cell type. We have previously shown that the sphingosine‐1‐phosphate receptor agonist Fingolimod/FTY720P promotes the generation of this particular Schwann cell phenotype by activation of dedifferentiation markers and concomitant release of trophic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 82 publications
1
36
0
Order By: Relevance
“…The efficacy of fibrin in promoting axon regeneration is increased by the platelets and mesenchymal stem cells that become entrapped in the fibrin clot in the nerve gap. They act by multiple mechanisms: (1) They release neurotrophic and other factors that act directly on the axons to promote regeneration [26].…”
Section: Restoration Of Function Without Surgical Interventionmentioning
confidence: 99%
“…The efficacy of fibrin in promoting axon regeneration is increased by the platelets and mesenchymal stem cells that become entrapped in the fibrin clot in the nerve gap. They act by multiple mechanisms: (1) They release neurotrophic and other factors that act directly on the axons to promote regeneration [26].…”
Section: Restoration Of Function Without Surgical Interventionmentioning
confidence: 99%
“…For mass spectrometry analysis, we used four independent biological replicates of MSCs. Confluent MSCs were washed three times with PBS in order to remove the FBS and were then incubated for another 48h in serum-free N2-medium [22,70,71] consisting of Dulbecco's modified Eagle's medium (DMEM, Gibco Cell Culture, Thermo Fisher Scientific, Darmstadt, Germany) containing 5 mg/mL insulin, 30 nM sodium selenite, 100 µM putrescine, 20 nM progesterone, and 5 µg/mL transferrin (all Sigma-Aldrich Chemie GmbH). Medium was changed again after 48 h to further exclude FBS effects, and was then incubated for another 48 h in N2 medium.…”
Section: Preparation Of Mesenchymal Stem Cell Secretome and Proteomementioning
confidence: 99%
“…To analyze secreted proteins within this second N2 medium preparation by mass spectrometry, we performed trichloroacetic acid (TCA) precipitation as previously described [70,71]. Briefly, conditioned medium was transferred to a 50 mL tube, centrifuged at 950× g at 4 • C for 10 min, and filtered through a 0.2 µm filter (Pall Acrodisc).…”
Section: Preparation Of Mesenchymal Stem Cell Secretome and Proteomementioning
confidence: 99%
“…Secretomics is a sub-field of proteomics that involves the analysis of the secretome including the liquid chromatography–mass spectrometry (LC-MS/MS) analysis, enzyme-linked immunosorbent assay (ELISA) or protein array ( 16 , 17 ). Since secretome plays a myriad of roles ranging from homeostasis to biological regulation, such as intercellular cross-talk ( 12 ), coordination of biological activity ( 18 ) and disease development ( 19 ), secretomics has been a good source for characterizing and quantifying proteins secreted by a given cell under specific experimental conditions and a powerful strategy for discovering disease biomarkers ( 20–22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, glial secretome has been a topic of active interest in biomarker discovery ( 17 , 23 , 24 ). Accordingly, a number of proteomics studies have identified numerous secretory proteins related to various neurological disorders ( 19 , 25–29 ). For instance, amyloid peptides and their precursors, tau proteins ( 30 ), have been identified as potential biomarkers for Alzheimer’s disease and alpha-synuclein ( 31 ) and apolipoprotein H ( 32 ) for Parkinson’s disease ( 33 ).…”
Section: Introductionmentioning
confidence: 99%